Primary School Teachers' Views on Empowering Leadership and Empowerment - Karagozoglu, Ahmet Alper; Ozan, Mukadder Boydak (Ani Publishing, 2024)
The aim of this study was to investigate the Primary School Teachers' views on empowerment and empowering leadership. The study adopted a phenomenological design, one of the qualitative research methods. The study was carried out with 13 volunteer Primary School Teachers working in different schools in the city center of Elazig in the 2020-2021 academic years. The criterion sampling technique, one of the purposive sampling methods, was used in sample selection. A semi-structured interview form consisting of open-ended questions was used in data collection. The results showed that when school principals exhibited fairness, offered opportunities for professional growth, delegated authority with corresponding responsibility, and maintained open communication channels, they positively reinforced the capabilities and morale of the teachers. School principals should know they are in a collaborative partnership with the teachers, and that organizational goals can only be achieved through joint efforts. Empowering leadership behaviors contribute to promoting managerial and organizational effectiveness. However, it was found that some principals unconsciously discriminated in terms of empowering their teaching staff. Additionally, the school principals generally held favorable attitudes towards unions. Considering these findings, it is recommended that school principals avoid holding union membership titles while performing their duties.
Keywords: Empowering leadership; empowerment; teacher empowerment